Staphylococcus aureus nasal carriers and the prevalence of methicillin resistant Staphylococcus aureus among medical students - R., Baag Shaza; Bansal, Vishvesh P.; Bhalchandra, Manjushree; Mishra, Jyotsna (International Journal of Research in Medical Sciences, 2017)
Background: Staphylococcus aureus is a dynamic and adaptable bacterium that has an incredible talent to attain antibiotic resistance. Nasal colonisation of S.aureus increases with greater exposure of students to the hospital environment. The prevention of staphylococcal infection and reduction of spread and emergence of MRSA are essential. Medical students would be a key target group to introduce awareness of hospital-acquired infections. Therefore, the present study aims at understanding the prevalence of carrier rate of S.aureus and MRSA among Medical students during their clinical postings. Methods: Nasal swabs were taken from 150 medical students. Their Staphylococcus aureus nasal carriage was determined by plating on sheep blood agar and MRSA carriage by to Kirby Bauer Disc Diffusion method using Cefoxitin disc (30 µg). Results: The present study showed a 40% nasal carriage of S.aureus amongst medical students. Of the 60 S. aureus isolates 28%, 36% and 56% isolates were from 1st, 2nd and 3rd year respectively. The colonisation rate of MRSA in the present study was found to be 12.66% amongst the medical students of 6%, 10%, 22% belonged to 1st, 2nd, and 3rd respectively Conclusions: The nasal carriage of Staphylococcus aureus and methicillin resistant Staphylococcus aureus (MRSA) among medical students increases as their exposure to patient care increases. Medical students should be made aware of the risks of carrying S.aureus and MRSA and educated about the hand washing protocol and safety precautions to be followed while handling patients.